Material Inventions: Applying Creative Arts Research - Barrett, Estelle; Bolt, Barbara (London Tauris & co, 2014)
The measurement of the significance and 'impact' of research is absolutely paramount in today's academic world - as evidenced by the recent introductions of research assessment exercises in the UK, Australia, Hong Kong and New Zealand. Material Inventions: Applying Creative Arts Research offers new and original ways of conceptualizing impact and innovation in creative arts research. This important book demonstrates how artistic research is capable of solving real-life problems and presenting transforming accounts of the world. What are the inventions and innovations of artistic research? What are the interdisciplinary applications of practice-led research methodologies and outcomes? In what ways can the methods and outcomes of artistic research benefit the broader community and creative and other industries? How can the impact of creative practice as research be demonstrated and more clearly articulated?By articulating the inventions, innovations, application and broader uptake of artistic research in and beyond the field of art, expert contributors advance the claim that artistic research constitutes a new paradigm or 'successor science' that impacts on interdisciplinary research and in diverse community and industry settings. In often surprising and unpredictable ways, the inventions and innovations of artistic researchers are being taken up beyond the creative arts in areas such as fire fighting, computer interfacing and design, public relations, medical science, caring for the aged, local history making, museology, biofeedback technologies and a range of therapeutic settings. This is a timely follow-up to Practice as Research: Approaches to Creative Arts Enquiry and will be indispensible to researchers, institutions and research assessment bodies.IntroductionExtending the Field: Invention, Application and Innovation in Creative Arts EnquiryEstelle Barrett Chapter 1 Beyond Solipsism in Artistic Research: The Art Work and The Work of Art Barbara BoltChapter 2 Blogging as Art, Art as ResearchLucas IhleinChapter 3 Conversations Before the End of Time: Refuturing Applications of a New Media Praxis Keith ArmstrongChapter 4 Multimodal Research Applied to Decision Making by Incident Controllers on the Fire GroundValerie InghamChapter 5 Newspaper Printing Sites and The Spoils of Creative ResearchDeborah Beaumont Chapter 6 The Riches Of Ambiguity: Art as a Site for the Senses Jo-Anne DugganChapter 7 Real Fiction: Theatre and Creative Research Scott WelshChapter 8 Practice as Method: The Ex/centric Fixations Project Bree HadleyChapter 9 Poetic Documentary And Visual Anthropology: Evoking The SubjectCameron RoseChapter 10 Marking Exchange: Life-Drawing, Methexis and Intersubjective Praxis Margaret MayhewChapter 11 Making Sense: Exploring Materialist Pedagogies Through Imagination, Collaboration and CriticalityCarole Gray and Gordon BurnettChapter 12 The Effective and The Evocative: A Spectrum of Creative Practice Research Jillian Hamilton and Luke JaanisteChapter 13 The Mode of Invention of Creative ResearchIris van der Tuin
Keywords: Artistic research